2000
DOI: 10.1007/s002040050001
|View full text |Cite
|
Sign up to set email alerts
|

An intra-laboratory validation of the Integrated Model for the Differentiation of Skin Reactions (IMDS): discrimination between (photo)allergic and (photo)irritant skin reactions in mice

Abstract: We recently presented a modified local lymph node test which made it possible to quickly and reliably differentiate between irritative and allergic skin reactions with extremely simple parameters. The Integrated Model for the Differentiation of Skin Reactions (IMDS) test combines measurement of cell proliferation in draining lymph nodes with measurement of primary ear swelling after topical application of the test substance on three consecutive days. In contrast to the 'classic' skin sensitisation test in guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 20 publications
3
30
0
Order By: Relevance
“…Hariya et al (1999) reported that IL-2 production with lymph node weight and CD4 positive subset ratio in LNC improved sensitivity. Homey et al (1998) and Vohr et al (2000) presented an integrated model for differentiating skin reaction (IMDS), which assesses ear swelling and cell proliferation in lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Hariya et al (1999) reported that IL-2 production with lymph node weight and CD4 positive subset ratio in LNC improved sensitivity. Homey et al (1998) and Vohr et al (2000) presented an integrated model for differentiating skin reaction (IMDS), which assesses ear swelling and cell proliferation in lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of this assay (integrated model for the discrimination of skin reactions; IMDS) verified that methods other than radioactive labelling may be comparably sensitive van Och et al 2000;Vohr et al 2000;Ulrich et al 2001b), and that it is possible to eliminate 'false positive' results induced by irritants. Thus, we asked whether there may be a simplified model analogous to the modified LLNA or IMDS also possible for the respiratory sensitization.…”
Section: Introductionmentioning
confidence: 84%
“…The underlying mechanisms and the complicated network of cytokine regulation it is now basically understood (Takashima 1995;Homey et al 1997;Leung 1998;Blu¨mel et al 1999). This knowledge about molecular and morphological differentiation during the onset of inflammatory reactions (Avnstrop et al 1989;Ulrich et al 1998;Gerberick et al 1999) led to simplified models for the discrimination between allergic and irritant pathways (Avnstrop et al 1989;Homey et al 1998;Vohr et al 2000). In principle, comparable mechanisms should exist in the mucosa, although carried out by other cell types (epithelial cells, smooth muscle cells, alveolar macrophages, lung fibroblasts etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact that the in vivo method cytokine studies used cells that had 'seen' BrdU while those in the ex vivo method never 'saw' the agent (and therefore did not become functionally modified it) might be an additional critical factor that works in the favor of the use of the ex vivo BrdU method to assess 'truer' measures of function of lymphocytes from hosts being used to assess a potential for ACD caused by a test chemical. Homey et al (1998) and Vohr et al (2000) presented an integrated model for differentiating skin (IMDS) reaction that assessed ear swelling and cell proliferation in lymph nodes to detect and differentiate chemical-induced irritant and allergic skin responses. In our study, since DI values were > 1 for all concentrations, DNCB is an allergic compound.…”
Section: Discussionmentioning
confidence: 99%